Resilience to Drought in Semi-Desert Sheep: Effects of Water Restriction During Pregnancy on Placental Efficiency in the Awassi Breed - Yetisgin, Sezen Ocak; Sen, Ugur (Wiley, 2020)
Assessing the resilience of Awassi sheep to water shortages during pregnancy, thereby investigating the effects of water scarcity on gestation efficiency in animals, could provide valuable and pertinent insight into future scenarios posed by climate change risks. In this study, 40 pregnant Awassi ewes randomly allocated to free watering group (C, n = 20) received water ad libitum and the water restricted group (WR) received 50% less water than the amount provided to group C. Water restriction decreased (p < .05) lambs' birth weights, placental weights (PWs), and cotyledon numbers (CNs). Placental efficiency (PE) and cotyledon efficiency (CE) were significantly higher in the WR group (p < .05). A marked difference in cotyledon weight - an increase of 12.1% - was recorded in the C group. The body weights of the pregnant ewes in the WR group decreased significantly (p < .05) by 22% during pregnancy. Significant increases (p < .05) in plasma ADH, cholesterol, Cl-, and Na+ levels were observed in the WR group ewes, indicating intense dehydration. We conclude that the Awassi breed of sheep can endure 50% water restriction during pregnancy and maintain successful parturition, a key outcome for sustainability.
Şen, Uğur/0000-0001-6058-1140; Ocak, Sezen/0000-0002-8201-4857;
Keywords: Climate Change; Cotyledon; Fetal Development; Placenta; Water Restriction